2003
DOI: 10.1046/j.0001-690x.2003.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in first‐episode psychosis

Abstract: Domains of self-rated QOL in FEP patients are differentially associated with malleable and non-malleable aspects of patient and illness characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 28 publications
11
37
4
2
Order By: Relevance
“…However other studies have found that patients with first-episode schizophrenia may also present with predominantly negative symptoms (Hovington et al, 2012; Malla et al, 2004). Studies have shown that patients with a higher PANSS total score or positive symptom score at baseline had greater reduction in global symptoms or positive symptoms after antipsychotic treatment (Levine and Rabinowitz, 2010; Walker et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…However other studies have found that patients with first-episode schizophrenia may also present with predominantly negative symptoms (Hovington et al, 2012; Malla et al, 2004). Studies have shown that patients with a higher PANSS total score or positive symptom score at baseline had greater reduction in global symptoms or positive symptoms after antipsychotic treatment (Levine and Rabinowitz, 2010; Walker et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, she emphasized that the relationship between negative symptoms and DUP is not well known. Prior studies have shown that negative symptoms at baseline are highly prevalent (Malla et al 2004b) and are associated with poor functional outcome (Malla et al 2004a), more resistance to treatment (Edwards et al 1999), more cognitive deficits (Heydebrand et al 2004), more social dysfunctioning (Addington and Addington 1993; Petersen et al 2008; Schmitz et al 2007) and poor quality of life (Schmitz et al 2007). She noted that positive symptoms are more responsive to treatment and have less impact on outcome.…”
Section: Outcomementioning
confidence: 99%
“…The subjective QoL of schizophrenic patients is described as associated with depression, anxiety, negative, and-rarely-positive symptoms [10,[22][23][24][25]. Other studies have related to the role of social support [17,26], DUP [27] and stress-related factors [28]. Most previous studies on factors affecting QoL were cross-sectional, included patients with various durations of illness, and analysed only one of the two dimensions of QoL.…”
Section: Introductionmentioning
confidence: 96%